Bargaining and Reputation: An Experiment on Bargaining in the Presence of Behavioural Types - Embrey, M.; Frechette, G. R.; Lehrer, S. F. (Review of Economic Studies, 2015)
We conduct a series of laboratory experiments to understand what role commitment and reputation play in bargaining. The experiments implement the Abreu and Gul (2000) bargaining model that demonstrates how introducing behavioral types, which are obstinate in their demands, creates incentives for all players to build reputations for being hard bargainers. The data are qualitatively consistent with the theory, as subjects mimic induced types. Furthermore, we find evidence for the presence of complementary types, whose initial demands acquiesce to induced behavioural demands. However, there are quantitative deviations from the theory: subjects make aggressive demands too often and participate in longer conflicts before reaching agreements. Overall, the results suggest that the Abreu and Gul (2000) model can be used to gain insights to bargaining behavior, particularly in environments where the process underlying obstinate play is well established.